1996
DOI: 10.3109/13682829609033157
|View full text |Cite
|
Sign up to set email alerts
|

Stuttering amelioration at various auditory feedback delays and speech rates

Abstract: The primary purpose of this study was to determine i f the finding of Kalinowski et al. (1993) of dramatic reductions in stuttering under delayed auditory feedback (DAF) at normal and fast speech rates could be replicated. The second purpose was to determine if stuttering frequency is differentially affected by various delays in an attempt to identify the optimal delay for fluency enhancement for both normal and fast speech rates. Fourteen adult stutterers read eight different passages at either a normal or fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 19 publications
8
70
2
Order By: Relevance
“…For DAF speakers hear their own speech with a short time delay. Delays are typically less than a quarter of a second (50-250 ms) (Burke, 1975;Kalinowski, Stuart, Sark, & Armson, 1996;Van Borsel, Reunes, & Van den Bergh, 2003). FAF is a form of AAF whereby the frequency range of the speaker's speech is shifted up or down leading to changes in pitch.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For DAF speakers hear their own speech with a short time delay. Delays are typically less than a quarter of a second (50-250 ms) (Burke, 1975;Kalinowski, Stuart, Sark, & Armson, 1996;Van Borsel, Reunes, & Van den Bergh, 2003). FAF is a form of AAF whereby the frequency range of the speaker's speech is shifted up or down leading to changes in pitch.…”
Section: Introductionmentioning
confidence: 99%
“…Long delays lead to reduced speech rate and prolongation of vowels, producing unnatural sounding speech (Goldiamond, 1965;Martin, Haroldson, & Triden, 1984;Perkins, Bell, Johnson, & Stochs, 1979). It has been suggested that reduced speech rate, rather than interference with an auditory feedback mechanism, causes the reduction in stuttering (Bloodstein, 1995;Costello-Ingham, 1993;Kalinowski et al, 1996;Wingate, 1970). Reduction in speech rate is known to improve fluency (Adams, Lewis, & Besozzi, 1973;Perkins et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial number of phenomena have been recognized that immediately eliminate or nearly eliminate stuttering and induce relatively fluent speech (i.e., 90 to 100% reduction in stuttering frequency) in those that stutter [1,2,7,8,18,19]. A wealth of replicated empirical reports and the near total absence of opposing reports substantiate these phenomena.…”
mentioning
confidence: 99%
“…For example, Lee (1950) was among the first to note the similarity of DAF effects to stuttering and since then a number of researchers have hypothesized the irregular use of auditory feedback as a cause of stuttering (Fairbanks, 1954;1955;Max et al, 2004). This view was paradoxically bolstered by reports that dysfluency could be reduced by providing people who stutter with DAF (Kalinowski et al, 1993;1996;Van Borsel et al, 2003;Alm, 2006). How altered auditory feedback reduces stuttering is the subject of intense debate.…”
Section: Discussionmentioning
confidence: 99%